C*-algebra generated by four projections with sum equal to 2 - Savchuk, Y. (Algebra and Discrete Mathematics, 2004)
We describe the C*-algebra generated by four orthogonal projections p₁,p₂,p₃,p₄, satisfying the linear relation p₁ + p₂ + p₃ + p₄ = 2I. The simplest realization by 2 × 2-matrixfunctions over the sphere S² is given.